2018
DOI: 10.1073/pnas.1808191115
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic theory of rerandomization in treatment–control experiments

Abstract: Although complete randomization ensures covariate balance on average, the chance of observing significant differences between treatment and control covariate distributions increases with many covariates. Rerandomization discards randomizations that do not satisfy a predetermined covariate balance criterion, generally resulting in better covariate balance and more precise estimates of causal effects. Previous theory has derived finite sample theory for rerandomization under the assumptions of equal treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(197 citation statements)
references
References 30 publications
(60 reference statements)
5
192
0
Order By: Relevance
“…Corollary Under rerandomization and condition 1,n1/2false(trueτ^τfalse)false|scriptM˙Vττ1/2false{false(1Rτ,-0.166667emboldx2false)1false/2ε+false(Rτ,-0.166667emboldx2false)1false/2LK,-0.166667emafalse}.Corollary 2 is a main result of Li et al . ().…”
Section: Sampling Distributions Of Regression Adjustment Under Rerandmentioning
confidence: 97%
See 3 more Smart Citations
“…Corollary Under rerandomization and condition 1,n1/2false(trueτ^τfalse)false|scriptM˙Vττ1/2false{false(1Rτ,-0.166667emboldx2false)1false/2ε+false(Rτ,-0.166667emboldx2false)1false/2LK,-0.166667emafalse}.Corollary 2 is a main result of Li et al . ().…”
Section: Sampling Distributions Of Regression Adjustment Under Rerandmentioning
confidence: 97%
“…Li et al . () derived the asymptotic distribution of trueτ^ under rerandomization, and showed that it is more precise than trueτ^ under the CRE. They further showed that, when a is small and x = w , the asymptotic variance of trueτ^ under rerandomization is nearly identical to Lin's (2013) adjusted estimator under the CRE.…”
Section: Framework and Notationmentioning
confidence: 99%
See 2 more Smart Citations
“…If the MSE of the resulting estimate is not much larger than that from the selection without the expensive predictor, then we may prefer the former selection to the latter so as to reduce the potential for bias due to imbalance at the expense of slightly larger variance of the treatment effect estimator. An alternative approach to avoiding imbalance considers re-randomization until some criterion capturing the degree of balance is met (e.g., Bruhn and McKenzie (2009), Rubin (2012, 2015) and Li, Ding, and Rubin (2016)). Our criterion for the covariate selection procedure in Step 2 can readily be adapted to this case; however, the details are not worked out here.…”
Section: Iiic Discussionmentioning
confidence: 99%